Single-incision trocar-less endoscopic management of giant liver hydatid cyst: a step beyond? - Ramia, Jose Manuel (Laparoscopic Surgery; Vol 2 (September 2018): Laparoscopic Surgery, 2018)
Acharya et al. present the manuscript “Single-incision trocar-less endoscopic management of giant liver hydatid cyst in children” (1) and I would like to make some comments about the manuscript and minimal access surgery in liver hydatidosis.